Effect of calcium carbonate as pore-forming agent on properties of recycled polyethylene terephthalate masterbatch. Issue 1 (February 2021) - Fang, Ting; Li, Jifeng; Yan, Wenjing; Gu, Diankuan; Du, Zhaofang
Abstract: In order to study the effect of calcium carbonate particles as pore-forming agent on properties of recycled polyethylene terephthalate(PET) masterbatch, pore-forming agent and PET derived from waste bottle were melt-blended and extruded, and then treated with acetic acid solution to obtain recycled PET masterbatch with micro-cavity structure. The influence of content of pore-forming agent and parameters of twin screw extruder for granulation process on the performance of recycled PET melt and masterbatch were analyzed. The results show that the intrinsic viscosity of recycled PET masterbatch is greatly affected by pore-forming agent and the parameters of the twin screw extruder for granulation process. When the mass ratio of polyester bottle flakes to virgin PET is 9:1 and 3 wt% of pore-forming agent added, with the temperature of the barrel 1 6 of the twin-screw extruder is 240°C, 244°C, 244°C, 244°C, 240°C, 240°C, respectively, and 150 r/min of screw speed, the intrinsic viscosity of the recycled PET masterbatch produced by twin screw extruder can reach 0.613 dL/g. The recycled PET masterbatch could be applied to PET fibers spinning. This method provides a new method for improving moisture regain for PET.